Mapping the digital divide in Britain: implications for learning and education - Eynon, R (2009)
The internet presents many potential opportunities for people to learn for both formal and informal purposes. However, not everyone is able to make the most of the internet for learning. This paper utilises quantitative nationally representative survey data of internet use in Britain in order to explore the digital divide in relation to learning activities online. The results from this analysis give a detailed picture of the digital divide in Britain; illustrating those who are non-users and users of the internet and the reasons that are important in explaining the diversity in non-use and use of the internet for learning (e.g., age, educational background, skills, attitudes and experience). The findings may assist in the development of policies that seek to support under-served groups to make the most effective use of the internet for formal and informal learning opportunities. © 2009 Taylor and Francis.